Teaching and learning about community development online: Insights and lessons learned - Judith Kulig; Eugene Krupa; Nadine Nowatzki (The Canadian Network for Innovation in Education (CNIE), 2007)
This paper discusses the development, delivery, and evaluation of a successful graduate course in community development offered to students across Canada via the Internet. The review of literature points to common themes in distance education, community development and health promotion. The course, "Health Promotion: Community Development Approaches", is presented as a case example with descriptions of the curriculum, delivery methods, learning resources, activities and recommendations for future offerings of the course and for distance education in general. Although web-based distance education is challenging and requires instructors and learners to adapt, it can be an effective way to learn about concepts, and model the principles and ideology that are at the core of community development. Résumé : Le présent article aborde l'élaboration, la prestation et l'évaluation d'un cours de niveau supérieur traitant du développement communautaire offert aux étudiants de l'ensemble du Canada par Internet. L'examen de la documentation souligne les sujets communs dans l'éducation à distance, le développement communautaire et la promotion de la santé. Le cours « Health Promotion: Community Development Approaches » est présenté à titre d'exemple avec les descriptions du plan de cours, des modes de prestation, des ressources d'apprentissage, des activités et des recommandations pour les cours qui seront donnés ultérieurement et pour l'éducation à distance en général. Bien que l'éducation à distance effectuée au moyen du Web présente des défis et qu'elle exige des instructeurs et des apprenants qu'ils s'adaptent, il peut s'agir d'une méthode efficace pour en apprendre sur les concepts et pour présenter les principes et idées à la base du développement communautaire.